The cable transport and its role in sustainable urban mobility (2016)
An abstraction on the development of mobility in towns and cable transport systems, their origin and evolution, its characteristics and its consistency with the new global and political trends in urban mobility is presented. A description of the main advantages of this type of systems is made and are highlighted by the presentation of case studies on global and Latin American framework. It is concluded that the cables transport systems and their various types, present adequate support against the mechanisms and strategies that make plans for sustainable urban mobility in cities, showing the main advantages being effective, safe, comfortable, fast systems and with significant benefits to the environment, an alternative that could contribute to improving the conditions of urban mobility in the cities of Latin America.